1979
DOI: 10.1080/03601237909372114
|View full text |Cite
|
Sign up to set email alerts
|

Sequential participation of glutathione and sulph‐hydryl (S) in reductive dechlorination of 2, 4‐di‐, and 2, 4, 5‐trichloro phenacyl chlorides by soluble fraction (105,000 x g) of chicken liver homogenate.

Abstract: The mode of reductive dechlorination of alpha-chloroacetophenones, 2,4-di-, and 2,4,5-trichloro phenacyl chlorides into respective acetophenone by soluble fraction (105,000 x g) from chicken liver homogenate has been investigated. The transformation involved the sequential participation of glutathione and a sulph-hydryl. The phenacyl chloride first reacted with glutathione to yield the phenacyl glutathione, which in turn, in the presence of a sulph-hydryl, was reduced enzymatically to produce the ketone, proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Previous studies showed that the reduction of toxic α-haloketones to nontoxic acetophenones requires glutathione (11,(16)(17)(18). In the initially proposed reaction mechanism, α-haloketones react nonenzymatically with glutathione to yield S-(phenacyl)glutathiones, which are the true substrates of an enzyme that was termed S-(phenacyl)glutathione reductase (SPG-R) (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the reduction of toxic α-haloketones to nontoxic acetophenones requires glutathione (11,(16)(17)(18). In the initially proposed reaction mechanism, α-haloketones react nonenzymatically with glutathione to yield S-(phenacyl)glutathiones, which are the true substrates of an enzyme that was termed S-(phenacyl)glutathione reductase (SPG-R) (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…If direct hydrolysis of I via P-0-vinyl cleavage to I11 had been the major route, a large amount of V and other metabolites would have been observed in the 3-h urine samples. In this connection it should be pointed out that the facile conversion of I11 to V via IV, in in vitro studies, is well established (Akhtar, 1979;Hutson et al, 1976).…”
Section: Resultsmentioning
confidence: 89%
“…It has been shown previously that I11 is very efficiently converted into a glutathione conjugate. The conjugate in turn is further metabolized to other products (Akhtar, 1979;Hutson et al, 1976). The fact that IV was not detected is also explained by the studies of Akhtar (1979), who showed that IV was efficiently reduced to V Residues of VI were not detected in the current study despite the fact that they had been shown to be present in in vitro studies with the soluble fraction from bovine liver homogenates (Akhtar and Foster, 1979).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation